Avaliação da percepção da qualidade de vida em pacientes diabéticos urêmicos, pré e pós transplante simultâneo pâncreas-rim - Posegger, Karin Romano [UNIFESP] (2017)
Introduction: Diabetic patients with chronic renal failure are considered chronic sufferers, both physically and psychologically, because of the physical pain due to neuropathy and microangiopathy. Amputations, cardiovascular diseases, and retinopathy are also consequences of prolonged exposure to the deleterious effects of diabetes and dialysis. Pancreas-kidney transplantation is considered the gold standard treatment for diabetics with end-stage renal disease. This is a therapeutic intervention aimed at maintaining a healthier lifestyle, without the burden of dialysis and insulin therapy, as well as increasing the life expectancy of these patients. However, the gain of this therapy in terms of Quality of Life (QoL) is still little investigated. This study aims to measure the QoL gain with the simultaneous pancreas-kidney transplantation (SPKT), not only from the generic point of view, but most notably to the specific gain consequent to each transplanted organ and also analyzing the maintenance of QoL over time, in the post-transplant period. Methods: Using the KDQOL-SF 36 - Kidney Disease Quality of Life – Short Form Health Survey, generic and specific for chronic kidney disease (CKD) and PAID – Problems Areas in Diabetes (diabetes-specific) QoL evaluation in 160 patients - 57 on the waiting list versus 103 submitted to the SPKT. This study evaluated the perception of the patient regarding general and specific QoL gain, specific for the control of CKD and diabetes in the pre-transplant and post-transplant intervals, which were subdivided into three time intervals: <1 year, between 1 and 3 years, and > 3 years. Results: The results of the Mean scores regarding the QoL perception of pretransplant and post-transplant patients (<1 year, between 1 and 3 years, > 3 years) and p values were, respectively: General Symptoms - SF-36: Physical Functioning (62.8 x 73.3, 85.2 and 82.6; p<0.001), Physical Function (51.3 x 84.8, 71.0 and 82.3; p<0.001), General Health (45.1 x 86.1, 72.4 and 65.6; p<0.001), Emotional Function (62.0 x 91.3, 72.0 and 84.8; p=0.001), Social Function (64.5 x 91.8, 84.0 and 84.3; p<0.001), Health Changes (52.2 x 100.0, 87.0 and 77.3; p<0.001); Specific Domains Regarding to the CKD: Symptoms/Problems (81.2 x 92.2, 87.2 and 84.8; p=0.004), Effects of Kidney Disease (61.5 x 96.7, 94.3 and 93.6; p<0.001), Burden of Kidney Disease (45.7 x 87.8, 89.3 and 78.8; p<0.001), Dialysis Team Support (89.3 x 100.0, 100.0 and 99.3; p<0.001), Health Related to the CKD (56.5 x 91.7, 83.2 and 80.4; p<0.001); and Diabetes Specific Control - PAID: Stress Caused by Diabetes Mellitus (42.3 x 34.8, 29.5, and 27.8, p = 0.011). Conclusions: Patients receiving simultaneous pancreas-kidney transplants had a better perception of quality of life, either in the generic and in the specific questionnaires for kidney disease and diabetes, when compared to patients on the waiting list for SPKT. This positive perception remained practically stable over time.